Asymmetry of perceptions: the impact on emotions, cognitions, and conflict - Jehn, Karen A. (Henry Stewart Talks, 2014)
Cognitive load, Affect, Performance, Satisfaction, Asymmetry Perceptions, Multilevel research
Reviewed at 2020/09/30